2021
DOI: 10.1172/jci.insight.147671
|View full text |Cite
|
Sign up to set email alerts
|

NETs decorated with bioactive IL-33 infiltrate inflamed tissues and induce IFN-α production in patients with SLE

Abstract: Interleukin-33 (IL-33), a nuclear alarmin released during cell death, exerts context-specific effects on adaptive and innate immune cells eliciting potent inflammatory responses. We screened blood, skin and kidney tissues from patients with Systemic Lupus Erythematosus (SLE), a systemic autoimmune disease driven by unabated type I interferon (IFN) production, and found increased amounts of extracellular IL-33 complexed with Neutrophil Extracellular Traps (NETs), correlating with severe, active disease. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 81 publications
(139 reference statements)
0
32
0
Order By: Relevance
“…discovered an increase of neutrophil extracellular traps (NETs) decorated with bioactive IL-33 in the blood of SLE patients, which showed a positive correlation with SLEDAI scores ( 15 ). NETs decorated with IL-33 were potent in activating plasmacytoid dendritic cells (pDCs) to produce type 1 interferons (IFN-I), which play key roles during SLE pathogenesis ( 15 , 44 ). Interestingly, this group also detected IL-33-decorated NETs in inflamed skin and inflamed kidney of SLE patients.…”
Section: Induction Phasementioning
confidence: 99%
“…discovered an increase of neutrophil extracellular traps (NETs) decorated with bioactive IL-33 in the blood of SLE patients, which showed a positive correlation with SLEDAI scores ( 15 ). NETs decorated with IL-33 were potent in activating plasmacytoid dendritic cells (pDCs) to produce type 1 interferons (IFN-I), which play key roles during SLE pathogenesis ( 15 , 44 ). Interestingly, this group also detected IL-33-decorated NETs in inflamed skin and inflamed kidney of SLE patients.…”
Section: Induction Phasementioning
confidence: 99%
“…IL-33 is a nuclear-targeted cytokine abundantly expressed at mucosal barriers, which can be released from intact cells to propagate inflammation [ 21 , 22 ]. Interestingly, the role for cleaved IL-33 alarmin decorating NETs in human systemic lupus erythematosus, linking neutrophil activation, type I IFN production and end-organ inflammation has been demonstrated [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the role for cleaved IL-33 alarmin decorating NETs in human systemic lupus erythematosus, linking neutrophil activation, type I IFN production and end-organ inflammation has been recently demonstrated by Georgakis et al [ 23 ]. Ozasa et al [ 28 ] found that IRF3/7, which are signal transducers downstream of TBK1, are required for IL-33 release from lung fibroblasts in response to cGAMP, which functions as an allergy-prone adjuvant inducing strong type-2 immune responses to co-inhaled allergen in the airway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study found increased amounts of extracellular IL-33 complexed with NETs in blood, skin and kidney biopsies from SLE patients, which correlated with the disease activity. Ex vivo analysis confirmed that neutrophils from SLE patients released IL-33-decorated NETs, further inducing a robust type I IFN response by DCs through their ST2 activation [ 85 ]. Conversely, other studies found no statistically significant difference in the serum level of IL-33 between SLE patients and controls [ 60 ], or even lower levels in the serum of patients [ 86 , 87 ].…”
Section: Expression Of Il-33 and St2 In Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Together with products of cell damage, ICs stimulate neutrophils to produce NETs. Once complexed with IL-33, NETs are potent activators of DCs via their ST2 receptor, leading to a potent IFN-α secretion that contributes to the IFN signature of SLE [ 85 ]. In addition, functional studies showed that DCs also responded directly to IL-33 through the ST2 receptor and polarized CD4+ T cells into a Th2 phenotype [ 97 ].…”
Section: The Pathophysiological Role Of Il-33 In Systemic Lupus Eryth...mentioning
confidence: 99%